Adjuvant chemotherapy after curative D2 gastrectomy in Latin American patients with gastric cancer - Serrano, M (2022)
Background: Gastric cancer (GC) is the fourth most common cause of cancer deaths around the world and the first cause of cancer deaths in Peru